Establishing The Export Agent of Indonesia's Moderate Islam Since The Elementary School Age - Shulhan, Shulhan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Moderate Islam is expected to be an alternative response to the phenomenon of radical Islamic movements, which tend to eliminate the spirit of Islamic value as a blessing for the entire world. A number of Muslim groups around the world choose to practice Islam exclusively and look at themselves as the most righteous in accordance with religious law. They tend to consider those who disagree with them as enemies who must be killed. Indonesia has recently developed a moderate Islamic discourse, through government and religious organizations such as Nahdlatul Ulama and Muhammadiyah, to stem right mainstream or left mainstream of Islam movement. This study was aimed to discuss the educational possibilities for preparing Indonesian cadres to speak out for Islamic moderation in the global world. This study employed a qualitative method with a library research approach, which was putting academic texts as the primary source. The study's findings were as follows: To export religious moderation to the global world, a holistic integrative strategy must be implemented starting from basic education school for establishing cadre of Indonesia’s moderate Islam voice, including 1. Learning and applying moderate Islamic values in daily life through structured programs. 2. Strengthening the Muslim intellect in various fundamental subjects, particularly English, Arabic, and mathematics enabling them to develop knowledge and skills to reach all segments of stratified mankind to spread moderate Islamic values in an applicable and inclusive manner. 3. Improving academic and popular writing skills in international languages that make their ideas more accepted by the entire global community and they have bargain among global